Thalassemia-an untoward situation among the pregnant women in North Bengal district, West Bengal, India - Biswas, Dilip K.; Sau, Arkaprabhu; Deb, Lily M.; Mandal, Onkarnath; Chakraborty, Bidhan (International Journal Of Community Medicine And Public Health, 2025)
Background: Thalassemia, an inherited hemoglobin disorder, affects approximately 7% of the global population. In India, thalassemia prevalence ranges from 3-4%, with significant variation among different communities and regions. This study aims to document the prevalence of thalassemia carriers among pregnant women in the Dakshin Dinajpur district of West Bengal, India. Methods: A cross-sectional study was conducted from January 2023 to November 2023. Pregnant women were screened for thalassemia at Block Primary Health Centers, and samples were analyzed at the Thalassemia Control Unit in Balurghat district hospital using High-Performance Liquid Chromatography (HPLC). Results were recorded in Thalamon software and analyzed for carrier rates and demographic correlations. Results: Out of 12,767 pregnant women tested, 29.6% (3,790) were identified as thalassemia carriers. The highest carrier rate was in Kushm and block (45.3%), while the lowest was in Banshihari block (22.9%). Hemoglobin E(Hb-E) carriers constituted 66% of carriers, followed by hemoglobin E disease (21%) and beta thalassemia carriers (9.6%). Significant correlations were found between carrier status and caste, with beta thalassemia being more prevalent among the Scheduled Tribes. Conclusions: The study highlights a high prevalence of thalassemia carriers among pregnant women in Dakshin Dinajpur, particularly Hb-E carriers. Genetic counselling and early screening are crucial to managing and reducing the transmission of thalassemia traits. The findings underscore the need for increased awareness and preventive measures, especially in high-risk communities. Further studies are recommended to develop strategies for reducing maternal complications and preventing carrier transmission.